Characterizing variants of unknown significance in rhodopsin: A functional genomics approach. Issue 8 (22nd June 2019) - Wan, Aliete; Place, Emily; Pierce, Eric A.; Comander, Jason
Abstract: Characterizing the pathogenicity of DNA sequence variants of unknown significance (VUS) is a major bottleneck in human genetics, and is increasingly important in determining which patients with inherited retinal diseases could benefit from gene therapy. A library of 210 rhodopsin ( RHO ) variants from literature and in‐house genetic diagnostic testing were created to efficiently detect pathogenic RHO variants that fail to express on the cell surface. This study, while focused on RHO, demonstrates a streamlined, generalizable method for detecting pathogenic VUS. A relatively simple next‐generation sequencing‐based readout was developed so that a flow cytometry‐based assay could be performed simultaneously on all variants in a pooled format, without the need for barcodes or viral transduction. The resulting dataset characterized the surface expression of every RHO library variant with a high degree of reproducibility ( r 2 = 0.92–0.95), recategorizing 37 variants. For example, three retinitis pigmentosa pedigrees were solved by identifying VUS which showed low expression levels (p.G18D, p.G101V, and p.P180T). Results were validated across multiple assays and correlated with clinical disease severity. This study presents a parallelized, higher‐throughput cell‐based assay for the functional characterization of VUS in RHO, and can be applied more broadly to other inherited retinal disease genes and other disorders. Abstract : Characterizing the pathogenicity of DNA sequence variants of unknown significance (VUS) is a major bottleneck in human genetics, and is increasingly important in determining which patients with inherited retinal diseases could benefit from gene therapy. A library of 210 rhodopsin (RHO) variants was created to efficiently detect pathogenic RHO variants that fail to express on the cell surface. This study presents a parallelized, higher‐throughput cell‐based assay for the functional characterization of VUS in RHO.